Nature of the power of the Registrar of Titles: judicial, quasi-judicial or administrative - Shahrul Natasha Halid; Jady Zaidi Hassim (Penerbit Universiti Kebangsaan Malaysia, 2021)
As a country with Torrens land registration system, the Registrar of Titles plays a key role in managing and maintaining the land registration in Malaysia. The powers and duties conferred upon the Registrar of Titles under the National Land Code 1965 are manifold, ranging from the power to conduct enquiries, the power to enter the Registrar’s caveat, the power to issue an arrest, the power to issue title and others. The nature of the power of the Registrar of Titles is often under judicial scrutiny due to the direct effect of the Registrar of Titles’ actions towards registration of instruments. The issue which seems to be fuddled is whether such power is considered as quasi-judicial or merely administrative? This paper undertakes to provide an answer to such a question. Content analysis will be used in this paper by evaluating the laws and case precedents in Malaysia and Australia. This paper concludes that due to the differences in the structure of the land administration organisation and also the provisions of the Malaysian National Land Code 1965 compared to those in Australia, there is a tendency for the courts in Malaysia to limit the nature of the power of the Registrar of Titles. Despite the myriad of powers and duties afforded to the Registrar of Titles in Malaysia, in reality, the powers are legally restricted and the position is merely considered as an automaton in the land registration system.